2022
DOI: 10.21203/rs.3.rs-1578453/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Interactions between carbon nanotubes and external structures of SARS-CoV-2 using molecular docking and molecular dynamics

Abstract: Molecular modeling techniques are used to describe the process of interaction between nanotubes and the main structures of the Covid-19 virus: the envelope protein, the main protease, and the Spike glycoprotein. Molecular docking studies show that the ligands have interaction characteristics capable of adsorbing the structures. Molecular dynamics simulations provide information on the mean squared deviation of atomic positions ​​between 0.5 and 3.0 Å. The Gibbs free energy model and solvent accessible surface … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 52 publications
0
1
0
Order By: Relevance
“…[179] The advantages of using CNTs over nanoparticles to inhibit the HIV-1 virus seen here correspond to their geometric complementarity and strong van der Waals force interactions with the protease active site. [180] Likewise, molecular docking studies by Lobato et al [181] revealed that the zigzag-like shape of CNTs favorably interacted with the M PRO , E PRO , and S-gly proteins. Their findings were important in selecting the best type of CNTs for COVID-19 antiviral treatment.…”
Section: Applications Of Cnts In the Treatment Of Covid-19mentioning
confidence: 99%
“…[179] The advantages of using CNTs over nanoparticles to inhibit the HIV-1 virus seen here correspond to their geometric complementarity and strong van der Waals force interactions with the protease active site. [180] Likewise, molecular docking studies by Lobato et al [181] revealed that the zigzag-like shape of CNTs favorably interacted with the M PRO , E PRO , and S-gly proteins. Their findings were important in selecting the best type of CNTs for COVID-19 antiviral treatment.…”
Section: Applications Of Cnts In the Treatment Of Covid-19mentioning
confidence: 99%